The use of 32P and 15N to Estimate Fertilizer Efficiency in Oil Palm - Elsje L. Sisworo; Widjang H. Sisworo; Havid Rasjid; Haryanto Haryanto; Syamsul Rizal; Z. Poeloengan; Kusnu Martoyo (PPIKSN-BATAN, 2004)
Oil palm has become an important commodity for Indonesia reaching an area of 2.6 million ha at the end of 1998. It is mostly cultivated in highly weathered acid soil usually Ultisols and Oxisols which are known for their low fertility, concerning the major nutrients like N and P. This study most conducted to search for the most active root-zone of oil palm and applied urea fertilizer at such soils to obtain high N-efficiency. Carrier free KH232PO4 solution was used to determine the active root-zone of oil palm by applying 32P around the plant in twenty holes. After the most active root-zone have been determined, urea in one, two and three splits were respectively applied at this zone. To estimate N-fertilizer efficiency of urea labelled 15N Ammonium Sulphate was used by adding them at the same amount of 16 g 15N plant-1. This study showed that the most active root-zone was found at a 1.5 m distance from the plant-stem and at 5 cm soil depth. For urea the highest N-efficiency was obtained from applying it at two splits. The use of 32P was able to distinguish several root zones: 1.5 m – 2.5 m from the plant-stem at a 5 cm and 15 cm soil depth. Urea placed at the most active root-zone, which was at a 1.5 m distance from the plant-stem and at a 5 cm depth in one, two, and three splits respectively showed difference N-efficiency. The highest N-efficiency of urea was obtained when applying it in two splits at the most active root-zone.